Immunologic memory in Haemophilus influenzae type b conjugate vaccine failure. Issue 5 (1st May 2003) - McVernon, J; Johnson, P D R; Pollard, A J; Slack, M P E; Moxon, E R
Abstract : Aims: To compare the convalescent antibody response to invasive Haemophilus influenzae type b (Hib) disease between conjugate vaccine immunised and unimmunised children, to look for evidence of priming for immunologic memory. Methods: Unmatched case-control study in the UK and Eire 1992–2001 and Victoria, Australia 1988–1990. A total of 93 children were identified as having invasive Hib disease following three doses of conjugate vaccine in infancy through post licensure surveillance throughout the UK and Eire; 92 unvaccinated children admitted to an Australian paediatric hospital with invasive Hib disease were used as historical controls. Convalescent serum was taken for measurement of Hib antibody concentration, and clinical information relating to potential disease risk factors was collected. The geometric mean concentrations of convalescent Hib antibodies were compared between immunised and unimmunised children, using raw and adjusted data. Results: Hib conjugate vaccine immunised children had higher serum Hib antibody responses to disease (geometric mean concentration (GMC) 10.81 μg/ml (95% CI 6.62 to 17.66) than unimmunised children (1.06 μg/ml (0.61 to 1.84)) (p < 0.0001). However, following adjustment for the significant confounding influences of age at presentation and timing of serum collection, a difference persisted only in children presenting with meningitis (vaccinated GMC 3.78 μg/ml (2.78 to 5.15); unvaccinated GMC 1.48 μg/ml (0.90 to 2.21); p = 0.003). Conclusions: Higher antibody responses to invasive Hib disease in vaccinated children with meningitis reflect priming for immunologic memory by the vaccine. Although a majority of children in the UK are protected from Hib disease by immunisation, the relative roles of immunologic memory and other immune mechanisms in conferring protection remain unclear.